2007
DOI: 10.1370/afm.681
|View full text |Cite
|
Sign up to set email alerts
|

Information Needs and Information-Seeking Behavior of Primary Care Physicians

Abstract: PURPOSE The aim of this study was to determine the information needs of primary care physicians in Spain and to describe their information-seeking patterns. METHODSThis observational study took place in primary care practices located in Madrid, Spain. Participants were a random stratifi ed sample of 112 primary care physicians. Physicians' consultations were video recorded for 4 hours. Clinical questions arising during the patient visit and the sources of information used within the consultation to answer ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
110
2
7

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(128 citation statements)
references
References 19 publications
9
110
2
7
Order By: Relevance
“…However, despite the growing popularity of online resources, many barriers remain that prevent clinicians from frequently and successfully answering clinical questions using online knowledge searches. These barriers include, but are not limited to, time limitations, uncertain knowledge accuracy, technology malfunction, and knowledge seeker forgetfulness of the questions needing answered [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the growing popularity of online resources, many barriers remain that prevent clinicians from frequently and successfully answering clinical questions using online knowledge searches. These barriers include, but are not limited to, time limitations, uncertain knowledge accuracy, technology malfunction, and knowledge seeker forgetfulness of the questions needing answered [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Questions most frequently asked were related to diagnoses and drug therapy. Also, in a video recorded observational study by González-González et al [15], whose aim was to determine the information needs of 112 primary care physicians during the patient consultation, the most frequent questions physicians had were related to diagnosis (53%) and treatment (26%). Our study supports these previous findings, however is differentiated in that it identifies information needs specific to a clinical visit notes and not general questions that arise during a patient encounter.…”
Section: Assessment and Plan As The Most Important Information In Ambmentioning
confidence: 99%
“…Previous research has not explicitly stated that physicians found HPI useful [15,43,58,59]. The HPI may be important to physicians because it includes a summary and background of what the patient is feeling, which can be helpful for diagnosis and treatment.…”
Section: Assessment and Plan As The Most Important Information In Ambmentioning
confidence: 99%
“…Again in 2007, Ely described the kinds of patient care questions physicians can't answer [8]. Also in 2007, Gonzalez reviewed 3500 patient consults in Spain to identify the most frequent questions asked by physicians there [9]. The cause of a certain symptom was the most frequently asked question according to their study.…”
Section: Literature Reviewmentioning
confidence: 99%